2015
DOI: 10.3892/etm.2015.2938
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane inhibits the antioxidant capacity of erythrocytes

Abstract: Abstract. The aim of the present study was to observe the effects of sevoflurane on the antioxidant capacity, endothelial nitric oxide synthase (eNOS) content and lifespan of erythrocytes. A 2% erythrocyte suspension was prepared from whole blood collected from healthy volunteers and then treated with sevoflurane at different concentrations (group A, 0%; group S1, 1%; group S3, 3%; and group S5, 5%), in the presence or absence of 200 µmol/l hydrogen peroxide (H 2 O 2 , or H in group names). In order to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…It has been reported that EI which is based on the viscosity method, is generally affected by Hct [14]. However, in the present study, there were no significant changes in Hct of the dexmedetomidine group before and postsurgery, when compared to group B (propofol) and control group.…”
Section: Discussioncontrasting
confidence: 82%
“…It has been reported that EI which is based on the viscosity method, is generally affected by Hct [14]. However, in the present study, there were no significant changes in Hct of the dexmedetomidine group before and postsurgery, when compared to group B (propofol) and control group.…”
Section: Discussioncontrasting
confidence: 82%
“…As a result, models of cellular oxidative stress and free radical scavenging are both useful for examining the antioxidant activity of polysaccharides and their mode of action. Without a nucleus, erythrocytes can withstand oxidative stress and preserve osmotic equilibrium thanks to a functioning enzymatic nd nonenzymatic metabolic system [11]. Meanwhile, the H 2 O 2 -induced oxidative stress model in HepG2 cells has been widely accepted [12].…”
Section: Introductionmentioning
confidence: 99%